Discovery Learning-Based Worksheets as a Tool for Enhancing Science Process Skills and Environmental Literacy in Middle School Students - Sry Ariyanti A. Muthalib; Nurasyah Dewi Napitupulu; Muslimin; Marungkil Pasaribu; I Komang Werdhiana (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this study is to develop Discovery Learning-based Learner Worksheets (LKPD) using the ADDIE model with the objective of enhancing the science process skills and environmental literacy of secondary school students. This research employs a one-group pretest-posttest design within the context of a research and development (R&D) project conducted in class VII of SMP Negeri 2 Bungku, comprising 29 students, of whom 13 are male and 16 are female. The research instruments included validation sheets, Discovery Learning-based learner worksheets, observation sheets for science process skills, environmental literacy tests, and questionnaires for teachers and students regarding their responses to the product. The results demonstrated the validity of this development, with a score of 88%, a figure that was additionally supported by the teacher response score, which fell within the "very practical" category. The product of this development has a positive effect on students' science process skills, with an N-gain of 0.60 in the moderate category, indicating a significant improvement. The effect size of 0.47 in the moderate category indicates that this improvement is very significant. Furthermore, the development results had a significant impact on students' environmental literacy, with an N-gain of 0.35 in the medium category. The effect size of environmental literacy was 0.47 in the medium category.